The Level of Mahr in Marriage : A Comparative Analysis of the Perspectives of the Shafi'i Madhhab and the Hanafi Madhhab - Na'imah, Farida Ulvi; Qoharuddin, Moch. Azis; Mustaqim Makki; Sunaji; Isnin Harianti (VRISPRAAK : International Journal of Law, 2023)
Dowry is one of the obligations in the marriage contract that is the wife's right to her husband. Although it is not a pillar of marriage, dowry has important symbolic and legal significance in Islam. This study aims to analyse the differences in views between the Shafi'i Madhhab and the Hanafi Madhhab regarding the level of dowry, the minimum limit, and the applicable provisions in each madhhab. This research uses a normative legal method with a descriptive-analytical and comparative approach to the sources of Islamic law from both madhhabs. The results show that the Shafi'i Madhhab does not set a minimum or maximum limit for dowry, provided that the goods or services provided have tradable value. Meanwhile, the Hanafi Madhhab sets a minimum dowry limit of ten dirhams and does not allow any amount below this. This study highlights the flexibility of Islamic fiqh in accommodating different social needs, while still maintaining the principles of justice and welfare in marriage.